Pengaruh Kebijakan Fiskal dan Pertumbuhan Ekonomi Terhadap Tingkat Pengangguran Terbuka di Indonesia - Minda Surelvi; Urmatul Uska Akbar (Media Riset Ekonomi Pembangunan (MedREP), 2025)
This study aims to examine the effects of: (1) government expenditure, (2) tax revenue, and (3) gross domestic product on the open unemployment rate in Indonesia. The data used in this research are time series data covering the period from 1988 to 2023. This is a quantitative study employing the Error Correction Model (ECM). The findings reveal that: (1) In the long run, government expenditure, tax revenue, and gross domestic product have a negative and significant effect on the open unemployment rate in Indonesia. (2) In the short run, tax revenue and gross domestic product have a negative and significant effect on the open unemployment rate in Indonesia, while government expenditure has no significant effect on the open unemployment rate. These findings highlight the importance of fiscal reforms oriented toward productive sectors and the enhancement of economic growth quality to sustainably reduce unemployment. Keywords: Government Expenditure, Tax Revenue, Gross Domestic Product, Error Correction Model (ECM)